Journal of Contemporary Private Law´s Presentation and General Editorial Guidelines - Rodrigues Junior, Otavio Luiz (Revista de Direito Civil Contemporâneo, 2020)
Private law, the most traditional and all-encompassing of legal subjects, has undergone significant changes over the past 100 years. Much was written in the twentieth century about the crisis in Private Law, especially concerning the inadequacy of classic civilistic solutions in addressing the problems that afflicted the short and conflictual 1900s, with all the wars, revolutions and changes in customs and social morality that occurred within that period. Yet the conflict surrounding private law actually dates back to the nineteenth century. In its early stages, there was a controversy between Romanists and historicists, who rejected codification, and the defenders of ius comune, who defended that Germany should have a civil code in line with the French one. At the end of the 1800s, however, these same groups were on opposite camps. Ironically, Romanists and historicists had now been placed in charge of codifying the German Private Law while the Germanists were excluded from the process. Many of them, such as Otto von Gierke, became critics of the Civil Code project, which they deemed individualistic and anti-social.